The irrelevance of political parties’ differences for public finances: evidence from public deficit and debt in Portugal (1974 – 2012) - Almeida, André Corrêa d' (2015)
This paper attempts to empirically test whether inter-parties’ political differences impact public finances in Portugal differently. Focused on public debt and the government budget deficit, and using data collected since 1974 for several variables, this paper applies econometric modeling to show that inter-parties’ differences have had no significant impact on the performance of public finances in Portugal. We observed that the Portuguese public budget deficit and the Portuguese public debt are mainly influenced by the process of globalization, the profile of the Portuguese Welfare State, and the phases of the economic cycle. In this context, this paper aims to dispel some myths regarding the “value” of a policy process based on political intrigue, enmity, and confrontation around differentiated political parties’ merits in European democracies.